Finite Element Analysis On T-Type Bone Plate Using Stainless Steel 316l - Ahmad Fikri; Desvina Yulisda; Agam Muarif; Rizka Mulyawan; Agus Adi Nursalim; Balqis Yafis; Sylvie Anastasya Utami; Apriani Riski; Nurmalita Nurmalita (LPPM Universitas Malikussaleh, 2024)
Bone fractures refer to the phenomenon of bone breakage or detachment caused by intensive loads. The primary causes of bone damage include incidents, traffic accidents, and sports injuries. One of the materials commonly used for bone support applications is 316L stainless steel. The design process for T-type bone supports involves creating mechanical drawings and simulations to demonstrate the material's behavior when subjected to mechanical and thermal loads during use by patients.In this study, the researchers aim to examine the mechanical and thermal properties of T-type bone plates using the Finite Element Analysis (FEA) method. The technical drawing of the T-type bone support is developed in Autodesk Fusion 360. The simulations involve the application of static and thermal loads. The loads applied to the T-type bone plate include compressive forces of 1 N, 10 N, 50 N, 85 N and 500 N, as well as temperatures of 28°C, 500°C, 800°C, 950°C, and 1400°C. The smallest stress is observed at a force of 1 N, resulting in a stress of 4.64 MPa, while the highest stress is recorded at a force of 500 N, producing a stress of 2319.70 MPa. Forces below 50 N are considered the safest to avoid deformation during loading. Additionally, temperatures below 912°C are optimal for the operation of bone supports.